AGAMA DAN TANTANGAN GLOBAL - Heru Syahputra (UIN Sumatera Utara Medan, 2020)
AbstractReligion is a form of belief that is believed by humans as a system of judgement that must be run into certain social behaviors, and is related to human historical experience. The intended trust must be as needed, and is also a truth. Therefore, the actualization of religious values that are subjective must be subjectively subjected to various Paradigms, visions, and conceps through certain structures or institutions that are easily understood especially in the era of globalization. Keywords : Religion, Globalization, History.